Study of the antitumor activity of the combination baicalin and epigallocatechin gallate in a murine model of vincristine-resistant breast cancer - Dima Awajan; Anas H. A. Abu-Humaidan; Wamidh H. Talib (Pensoft Publishers, 2024)
Background: Breast cancer is one of the primary causes of death in women worldwide. Yearly, a quarter of cancer cases in women are breast cancer. The problem is aggravated by the emergence of chemotherapeutic resistance. One of the practices to overcome this problem is using natural products along with chemotherapy. Epigallocatechin Gallate (EGCG) is the main efficient catechin in green tea. Baicalin is the main active chemical constituent of Scutellaria baicalensis. Both natural products have anti-cancer and improving resistance activities. Therefore, a combination of EGCG and baicalin may afford a possible way out to overcome chemotherapeutic resistance. Methods: EGCG and baicalin were tested on Vincristine-sensitive (EMT-6/P) and Vincristine-resistant (EMT-6/V) mouse mammary cell lines. Antiproliferative and apoptotic effects were assessed for EGCG, baicalin, their combination, and Vincristine in vitro using MTT and caspase-3 assays. An in vivo study was conducted to assess the effect of EGCG, baicalin, their combination, vincristine, vincristine along with the combination in both EMT-6/P and EMT-6/V mouse mammary cell lines. The safety profile was also considered using liver enzymes and creatinine assays. Results: in vitro, EGCG and baicalin had synergistic effects in both cell lines. The combination of baicalin and EGCG as 140 and 100 µM respectively, caused an apoptotic effect higher than the single treatment of baicalin 175 µM or EGCG 125 µM, in vincristine-resistant cell lines. In vivo, the combination along with vincristine significantly enhanced the reduction of tumour size in mice implanted with EMT-6/P and EMT-6/V cell lines. According to the safety profile, the combinations of EGCG and baicalin are safe. Conclusion: The combination of baicalin and EGCG can be optimistic in improving vincristine-resistant cells to treatments.